Biotransformation of food waste into biofertilisers through composting and anaerobic digestion: a review - Zaini, Nurul Solehah Mohd; Khudair, Abedelazeez J.D.; Mohsin, Aliah Zannierah; Jitming Lim, Elicia; Minato, Wakisaka; Idris, Hamidah; Syafawati Yaacob, Jamilah; Rahim, Muhamad Hafiz Abd (Czech Academy of Agricultural Sciences, 2023)
A growing world population means greater pressure on earths resources. Currently, 30 of food is wasted, which poses a significant risk to both humans and the environment. One way to offset the growth in food waste (FW) is through the process of microbial bioconversion, whereby FW is transformed into a range of nutrient-dense biofertilisers. This approach not only promotes a highly desirable circular economy, but it can also reduce the use of inorganic fertilisers, which adversely impact the environment through increased greenhouse gases, changes in soil and water characteristics, and loss of biodiversity. The bioconversion of FW to biofertiliser relies on the processes of aerobic (composting) and anaerobic digestion. Recently, alternative decomposition techniques included growing specific beneficial microbes, such as effective microorganisms, to speed up the breakdown process. Microorganisms can act as biostimulants and biodecomposers, possessing nutrient-fixing abilities and providing protection from biotic and abiotic stresses, thus enhancing plant growth and overall health. The potential uses of FW are complex and diverse, but research is actively done to effectively utilise this resource for biofertiliser applications.